THE RELATIONSHIP BETWEEN TURNOVER INTENTION AND EMPLOYEE WORK PRODUCTIVITY ON SUPPLY CHAIN MANAGEMENT EFFECTIVENESS (A Study on Manufacturing Companies in the Medan Industrial Area) - Siswa Pratama; Akhmad Taufik; Taha Mohd Omar (International Conference on Health Science, Green Economics, Educational Review and Technology, 2025)
This study aims to analyze the direct and indirect influence of Turnover Intention and Employee Work Productivity on Supply Chain Management (SCM) Effectiveness. SCM effectiveness is measured through the dimensions of reliability, responsiveness, flexibility, cost, and asset management. The population in this study consists of operational and managerial employees in the logistics/distribution sector. A sample of 150 respondents was taken using purposive sampling technique. Data were analyzed using Structural Equation Modeling (SEM) with the assistance of SmartPLS software. The results show that: (1) Turnover Intention has a negative and significant relationship with Work Productivity; (2) Turnover Intention has a negative and significant relationship with SCM Effectiveness; (3) Work Productivity has a positive and significant relationship with SCM Effectiveness; and (4) Work Productivity partially mediates the relationship between Turnover Intention and SCM Effectiveness. These findings imply that management needs to implement employee retention and productivity enhancement strategies to maintain optimal supply chain performance.